Effectiveness of Field Vaccination Against Jembrana Disease Virus in Bali Cattle in West Sulawesi, Indonesia - Fahrodi, Deka Uli; S Marsudi, Muhammad; A Rantam, Fedik; S Said, Nur (The Iraqi Journal of Veterinary Medicine, 2026)
Jembrana disease is an infectious disease caused by the Jembrana disease virus (JDV), this disease predominantly infects Bali cattle, thus threatening the Bali cattle population in Indonesia, especially in West Sulawesi. This study aims to assess the effectiveness of JDV vaccination by measuring the antibody response via enzyme-linked immunosorbent assay (ELISA), then carrying out a serum neutralization test (SNT) and molecular confirmation. the data was collected from 120 Bali cattle sera which had been vaccinated one, three, and six months prior to sampling. The amount of antibodies produced was analyzed by the ELISA test, while the neutralization assay of antibodies was analyzed by the SNT test in Vero cell cultures and verified by reverse transcriptase-PCR. the results indicated that at one month post-vaccination, the amount of antibodies was highest (mean optical density of 1.704 units), and then reduced at three months (1.223) and six months (0.672) post-vaccination. Seroprotective antibodies against Bali cattle at one month post-vaccination indicated 75% but reduced to 2.5% at three months post-vaccination and no longer existed at six months post-vaccination. SNT results from samples with seroprotective titters exhibited positive neutralization activity. Confirmation results utilizing the reverse transcriptase-PCR method indicated the absence of viral nucleic acid in seroprotective samples. The research findings indicate that JDV vaccination successfully elicits a humoral immune response; however, its duration of protection is constrained. To help get rid of Jembrana disease in the Bali cattle population, it is important to give booster vaccinations every 3 to 4 months and put in place integrated biosecurity measures‎‎‎.